Effect of iron nanoparticles and dry yeast extract on the yield and the productivity of corn (Zea maize L.) - Al-Shaheen, Mustafa R.; Asmail, Mokhald Hadi; Al-Shaheen, Mohammed R. (Iraqi Journal of Science, 2019)
This work was carried out at the Glass House at the Faculty of Agriculture/ Anbar University in the period between 2016 to 2017 Nano-iron and dry yeast extract were added to evaluate the response of maize productivity. Three concentrations of nano-iron, 0, 50, and 100 mg, were sprayed on the leaves The yeast extract of three concentrations 0, 100 and 150 grams per liter were sprayed on the leaves. The results showed the superiority of the treatments that were sprayed with nanoparticles with the highest rate of chlorophyll, the seed protein ratio and the percentage of seed oil. Significant levels were also recorded when spraying the plants with dry yeast extract. The interactions of 100 mg of nanotube and 150 g / l dry yeast extract characterized by the highest rate of chlorophyll, the oil content in the seeds (%)and the protein rate in the seeds (%)compared to other transactions.